The IVIG treatment response in autoimmune polyendocrine syndromes type 2 with anti-GAD65 antibody-associated stiff person syndrome: a case report and literature review - Yulong Yang; Hailin Jiang; Wenming Yang; Wenming Yang; Wenming Yang; Han Wang; Han Wang; Meixia Wang; Meixia Wang; Xiang Li; Peng Huang; Shuzhen Fang; et al. (Frontiers in Immunology)
Autoimmune polyendocrine syndromes (APS) is a rare group of disorders caused by impaired function of multiple endocrine glands due to disruption of immune tolerance. Of which, type 2 (APS-2) is the most common. Glutamic acid decarboxylase (GAD) is the rate-limiting enzyme for the synthesis of gamma-aminobutyric acid (GABA). Anti-GAD antibodies are associated with various neurological disorders, including stiff person syndrome (SPS). SPS is characterized by axial muscle stiffness, rigidity, and intermittent painful muscle spasms, with a prevalence of one to two in a million, making it an extremely rare neurological disorder. The comorbidity of APS-2 with SPS is even rarer. Most practicing neurologists encounter only one or two cases of APS-2 combined with anti-GAD65 antibody-associated SPS in their careers, resulting in underdiagnosis and undertreatment, leading to severe disability and suffering. This case report describes a young male who initially exhibited hair loss, vitiligo, and previously unreported eosinophilia. Before his diagnosis, he was admitted multiple times, with symptoms improving following the addition of intravenous immunoglobulin (IVIG) therapy to a poor treatment regimen. This paper aims to increase physicians’ awareness of this condition, enhancing the likelihood of early diagnosis and treatment.